A fuzzy analytic network process approach to determining prospective competitive strategy in China: a case study for multinational biotech pharmaceutical enterprises - Lee, Yun-Huei (Journal of Business Economics and Management, 2012)
This study explores efforts to identify the most appropriate competitive strategy relative to multinational biotech pharmaceutical enterprises’ strategy selection. The research uses the analytic network process (ANP) technique combining both qualitative and quantitative information to construct a hierarchical model involving interactions among various criteria for competitive strategy selection, and also introduces fuzzy logic to eliminate vagueness, subjectivity, and imprecision stemming from human judgment. The most important finding shows that the most suitable competitive strategy for multinational enterprises (MNEs) is innovative-focus strategy. Also, the weighted calculations present the three most important criteria affecting the competitive strategy of foreign direct investment (FDI): collaboration with local partners, governmental rules and regulations and high-quality research personnel with R & D capability.Article in English.Fuzzy metodo taikymas nustatant konkurencingumą skatinančias strategijas, naudojamas Kinijoje: tarptautinių farmacijos kompanijų pavyzdžiuSantrauka. Straipsnyje analizuojama galimybė nustatyti ir parinkti strategiją, kuri yra tinkamiausia tarptautinėms biotechnologinėms farmacijos kompanijoms ir padėtų joms konkurencinėje aplinkoje. Autoriai taikė analitinį tinklo formavimo metodą (ANP), derindami kokybinę ir kiekybinę informaciją bei duomenis, kurie buvo skirti hierarchiniam modeliui formuoti. Analizuojant įvairius verslo strategijos veiksnius ir pritaikius Fuzzy logicmetodą, buvo pašalinta neapibrėžtumo sąlyga, kuri dažnai siejama su subjektyvumu ir netikslumais, atsirandančiais dėl žmogiškojo veiksnio / sprendimo. Gauti rezultatai rodo, kad tarptautinėms biotechnologinėms farmacijos kompanijoms viena tinkamiausių strategijų, didinančių konkurencingumą, yra inovatyvi fokusinė strategija.Reikšminiai žodžiai: konkurencija, strategija,  Fuzzy metodas, tarptautinės kompanijos, farmacijos įmonės